Endocytotic uptake of HPMA-based polymers by different cancer cells: impact of extracellular acidosis and hypoxia - Gündel D (Dove Medical Press, 2017)
Daniel Gündel,1 Mareli Allmeroth,2 Sarah Reime,1 Rudolf Zentel,2 Oliver Thews1 1Institute of Physiology, Martin Luther University Halle-Wittenberg, Halle (Saale), 2Institute of Organic Chemistry, Johannes Gutenberg-University, Mainz, Germany Background: Polymeric nanoparticles allow to selectively transport chemotherapeutic drugs to the tumor tissue. These nanocarriers have to be taken up into the cells to release the drug. In addition, tumors often show pathological metabolic characteristics (hypoxia and acidosis) which might affect the polymer endocytosis.Materials and methods: Six different N-(2-hydroxypropyl)methacrylamide (HPMA)-based polymer structures (homopolymer as well as random and block copolymers with lauryl methacrylate containing hydrophobic side chains) varying in molecular weight and size were analyzed in two different tumor models. The cellular uptake of fluorescence-labeled polymers was measured under hypoxic (pO2 ≈1.5 mmHg) and acidic (pH 6.6) conditions. By using specific inhibitors, different endocytotic routes (macropinocytosis and clathrin-mediated, dynamin-dependent, cholesterol-dependent endocytosis) were analyzed separately.Results: The current results revealed that the polymer uptake depends on the molecular structure, molecular weight and tumor line used. In AT1 cells, the uptake of random copolymer was five times stronger than the homopolymer, whereas in Walker-256 cells, the uptake of all polymers was much stronger, but this was independent of the molecular structure and size. Acidosis increased the uptake of random copolymer in AT1 cells but reduced the intracellular accumulation of homopolymer and block copolymer. Hypoxia reduced the uptake of all polymers in Walker-256 cells. Hydrophilic polymers (homopolymer and block copolymer) were taken up by all endocytotic routes studied, whereas the more lipophilic random copolymer seemed to be taken up preferentially by cholesterol- and dynamin-dependent endocytosis.Conclusion: The study indicates that numerous parameters of the polymer (structure, size) and of the tumor (perfusion, vascular permeability, pH, pO2) modulate drug delivery, which makes it difficult to select the appropriate polymer for the individual patient. Keywords: HPMA–LMA copolymers, endocytosis, tumor microenvironment, tumor lines, structure–property relationship